Linking collective in vitro to individual in silico peptide bioactivity through mass spectrometry (LC-Q-TOF/MS) based sequence identification: the case of black cumin protein hydrolysates - (:unkn) unknown (SPRINGER, 2021)
Black cumin (Nigella sativaL.) is a seed that has been utilized in traditional medicine due to the bioactive characteristics of seed oil and therein solubilized components. In the present study, using enzymatic proteolysis (0-2 h) and fast protein liquid chromatography (FPLC)-based fractionation techniques, trypsin and papain hydrolysates of black cumin protein concentrates were investigated for their dual antioxidative and acetylcholinesterase (AChE) inhibitory activities. Peptides in the active fractions were identified using a liquid chromatography quadrupole time-of-flight mass spectrometry (LC-Q-TOF/MS) based analytical method, which further facilitated the in silico prediction of bioactivity for each and every characterized peptide sequence. While the extent of AChE inhibitory activity mostly decreased with proteolysis, various antioxidative activities increased during proteolytic treatments. Based on their relatively higher activities, 30 min papain treated hydrolysates were fractionated into four major fractions and their antioxidative capacities were verified in vitro. Peptide profiles of the fractions were investigated by LC-Q-TOF/MS analysis. Twenty different peptide structures were identified and their potential bioactivities were verified in silico. The interactions of the sample peptides with AChE were simulated via molecular docking. While anionic peptides were generated in this study, hydrophobic interactions possibly played a pivotal role in their dual bioactivities (i.e., AChE inhibitory and antioxidative) and peptide length could also be influential. [GRAPHICS] .
Keywords: Black cumin; Bioactive peptides; LC-Q-TOF/MS; In silico analysis; AChE-inhibitory activity; Molecular docking; ANTIMICROBIAL ACTIVITY; NIGELLA-SATIVA; ANTIOXIDANT; FOOD